Predictors of the Sense of Embodiment of a Female Victim of Sexual Harassment in a Male Sample Through 360-Degree Video-Based Virtual Reality - Ventura, Sara; Miragall, Marta; Cardenas, Georgina; Baños, Rosa M. (Frontiers in Human Neuroscience, 2022)
The sense of embodiment refers to the set of sensations related to having (i.e., ownership), being located in (i.e., location), and controlling (i.e., agency) a virtual body. Recently, 360-degree video-based Virtual Reality (VR) has been used to manipulate the sense of embodiment, generating the body-swap illusion, that is, the illusionary switch from the real body to a virtual one. However, the psychological mechanisms involved in this illusion are still unknown. The present study is a secondary analysis of the study by Ventura et al. (2021a) investigating the feasibility of 360-degree video to induce the body swap from a male's real body to a female virtual body in a sexual harassment virtual environment. In addition, the study explores whether the sense of presence and psychological trait variables related to sexual harassment (i.e., machismo, chivalry, alexithymia, empathic abilities) predict the illusion of owning the body of a female victim of sexual harassment. Forty-four men participated in the study, and the results indicate that the 360-degree video is able to induce the body-swap illusion for location and ownership, but not for agency. Multiple regression analyses showed that the sense of presence was a predictor of the three dimensions of embodiment, but specific psychological traits (i.e., low scores on machismo, high scores on difficulties expressing feelings, and high scores on perspective taking) were also predictor variables of experiencing a greater sense of location and agency in the female virtual body. This study shows that both technological issues and participants' psychological traits are involved in the experience of the body-swap illusion in a sexual harassment scenario using 360-degree video-based VR.